(untitled) (Altre Modernità, 2018)
This paper focuses on LinkedIn (LI), and in particular, on LI professional discussion Groups, i.e. dedicated spaces used by professionals to keep in touch with their peers, share information and updates, and debate topical issues. The analysis is based on a corpus comprising 557 interactions on four Groups of legal practitioners, Leadership for Lawyers, Legal IT & Innovation Network, Mediation Discussion Group (MDG), and International Arbitration. This study is set in the framework of Computer Mediated Discourse Analysis. The research questions are as follows: what motives guide LI Group members in their online activity and how can the social practices they engage in be defined? What rhetorical strategies are deployed in negotiating/communicating professional knowledge in Group conversations?. how do participants discursively construct for themselves an image of authoritativeness in the knowledge dissemination process? What is the impact, if any, of the architecture of the SNS and the affordances it makes available on the actual dynamics of Group interaction? Findings indicate that although members’ activities within LIN Groups are conventionally called “conversations”, the actual interaction is limited, as in most cases members simply share information and updates and bring issues or developments to the attention of other professionals. Results also show that very often professionals are active on LI Groups for reasons of self-promotion (personal branding) and, more interestingly, for the promotion of goods and services, thus giving rise to a clear case of genre bending (Bhatia 2004). A regards the organisation of posts, in many cases they are not self-standing, but rather symbiotic with other genres (e.g. articles, blog posts) or resources published on other websites. Further research is needed to verify if these findings are peculiar to legal practitioners’ Groups or apply to LI Groups in general.